Financial Performance Analysis Before And During The Covid-19 Pandemic In Public Companies In The Property Sector - chintya , Caroline; Maulida, Alfiatul; Primasari, Pristin (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines differences in the financial performance of public property sector companies before and during the COVID-19 pandemic. The objective is to analyze changes in Return on Equity (ROE), Net Profit Margin (NPM), Return on Assets (ROA), Gross Profit Margin (GPM), and Cash Ratio (CR). Using secondary data from eight companies listed on the Indonesia Stock Exchange for 2019–2020, the Wilcoxon Signed Rank Test was applied. The results show significant differences in ROE and NPM, while ROA, GPM, and CR do not differ significantly. These findings imply that profitability was more vulnerable to the pandemic, highlighting the need for stronger financial resilience strategies. Keywords: Financial Performance, COVID-19 Pandemic, Property Sector, Profitability Ratios, Liquidity, Wilcoxon Signed Rank Test, Indonesia Stock Exchange, Public Companies